Jewish apocalyptic and its history - Sacchi, Paolo (Journal for the study of the pseudepigrapha / Supplement series, 1990)
This translation of L'apocalittica giudaica e la sua storia makes Professor Sacchi's innovative thesis on Jewish apocalyptic available to a wider, English-reading audience. Sacchi argues that the term 'apocalyptic' is a modern invention, deriving from the wish to conceptualize the field of research on the affinities between the Apocalypse of John and other works of its time. These affinities do not just relate to literary character and form but also in part to content. Focusing on the material of 'Enoch' Sacchi concludes that what is needed is a more precise, literary and historical definition of 'apocalyptic'.